The advent of psychosurgery in Australia—with particular attention to its introduction into Sydney. (October 2016) - White, Richard T; McGee-Collett, Martin
Objective: The objective of this study was to describe the advent of prefrontal lobotomy in Sydney and, less comprehensively, its introduction into Australia. Method: Reference to journal articles, books, reports and archival data held at the Royal Prince Alfred Hospital and via internet searches, interviews and personal memory. Result: This paper describes the arrival of psychosurgery in Sydney in the mid-1940s, and less comprehensively, its arrival in other Australian cities. Conclusions: In New South Wales, from 1945 or 1946, prefrontal lobotomies were conducted in private clinics and in public hospitals but, because of legal and practical hurdles, it is unlikely that psychosurgery was performed in mental hospitals prior to December 1958. This paper gives some details regarding the participation of neurosurgeons and of the major public hospitals in psychosurgery, and touches on the attitudes within the Australian medical profession towards this dramatic new therapy.